2014
DOI: 10.1002/2014jd021489
|View full text |Cite
|
Sign up to set email alerts
|

Soil as a natural rain gauge: Estimating global rainfall from satellite soil moisture data

Abstract: Measuring precipitation intensity is not straightforward; and over many areas, ground observations are lacking and satellite observations are used to fill this gap. The most common way of retrieving rainfall is by addressing the problem "top-down" by inverting the atmospheric signals reflected or radiated by atmospheric hydrometeors. However, most applications are interested in how much water reaches the ground, a problem that is notoriously difficult to solve from a top-down perspective. In this study, a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
359
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 349 publications
(376 citation statements)
references
References 47 publications
14
359
3
Order By: Relevance
“…Figure 6 (statistics provided in Table 1) confirms the effect of surface saturation on adjusted precipitation, which is well described in previous studies (e.g., Brocca et al, 2013Brocca et al, , 2014. The recovered precipitation, when the surface soil is saturated, only contributes more noise rather than an improvement to the rainfall estimates.…”
Section: Effect Of Surface Soil Saturationsupporting
confidence: 86%
See 2 more Smart Citations
“…Figure 6 (statistics provided in Table 1) confirms the effect of surface saturation on adjusted precipitation, which is well described in previous studies (e.g., Brocca et al, 2013Brocca et al, , 2014. The recovered precipitation, when the surface soil is saturated, only contributes more noise rather than an improvement to the rainfall estimates.…”
Section: Effect Of Surface Soil Saturationsupporting
confidence: 86%
“…Studies have demonstrated that in situ (Brocca et al, 2009(Brocca et al, , 2013Matgen et al, 2012) and satellite (Francois et al, 2003;Pellarin et al, 2008Pellarin et al, , 2013Brocca et al, 2014) estimates of surface soil moisture could contribute to precipitation estimates by providing useful information concerning the sign and magnitude of antecedent rainfall accumulation errors. In particular, Brocca et al (2014) estimated daily rainfall on a global scale based on satellite SM products by inverting the soil water balance equation.…”
Section: W Zhan Et Al: Correction Of Real-time Satellite Precipitatmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Brocca et al (2014) developed a method for estimating rainfall accumulation amounts directly from satellite SM observations based on the principle that the soil can be treated as a "natural rain gauge". In contrast with classical satellite rainfall products, this new bottom-up approach attempts to measure rainfall by calculating the difference between two successive SM measurements derived from a satellite SM product.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, TC is applied to the rainfall accumulation estimates derived from (1) ERA-Interim (Dee et al, 2011), (2) SM2RAIN (Brocca et al, 2014) via inversion of Advanced SCATterometer (ASCAT; Wagner et al, 1999, SM data, (3) the NOAA Climate Prediction Center morphing (CMORPH, raw version) (Joyce et al, 2004) and (4) the TRMM Multi-satellite Precipitation Analysis (TMPA) 3B42RT (Huffman et al, 2007) product over the CONUS (note that 3B42RT and CMORPH do not include gauge information in their retrieval algorithms). Thanks to the ability of TC to provide the correlation against the "un- known" truth (ETC; McColl et al, 2014), the assessment of the products will be carried out in terms of correlation against "true" rainfall values.…”
Section: Introductionmentioning
confidence: 99%